Calculation of electron mobility and effect of dislocation scattering in GaN - Kundu, J.; Sarkar, C.K.; Mallick, P.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The electron mobility of GaN has been obtained at various temperatures by the
relaxation time approximation method. The effect of dislocation scattering has also been
discussed and calculated alongwith other important scattering mechanisms in this
material. The results agree with other available experimental and theoretical data.